2009
DOI: 10.1080/07357900802192190
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Properties ofGymnosperma GlutinosumLeaf Extracts

Abstract: The present study was undertaken to validate the antitumor potential of Gymnosperma glutinosum from regional people's account, using the in vitro and in vivo L5178Y-R lymphoma murine model. Non-polar G. glutinosum crude extracts were tested on L5178Y-R cells. We found significant (p < 0.05) cytotoxic activity (up to 40%) of the hexane extract, which was further fractioned; fraction 1 (F1) was then observed to produce up to 51% apoptosis-mediated L5178Y-R cytotoxicity in vitro at concentrations lower than 0.98 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 24 publications
0
22
0
1
Order By: Relevance
“…Previous studies reported that P. nigrum L. extract and piperine possess antitumor [17], anti-inflammatory [7] and immunomodulating potential [7,17,18]. Pathak and Khandelwal [6] reported anti-oxidative, anti-apoptotic and chemo-protective ability of piperine in blastogenesis, cytokine resease and restoration of spleen cells population, and they recommended the therapeutic usefulness of piperine in immuno-compromised situations.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies reported that P. nigrum L. extract and piperine possess antitumor [17], anti-inflammatory [7] and immunomodulating potential [7,17,18]. Pathak and Khandelwal [6] reported anti-oxidative, anti-apoptotic and chemo-protective ability of piperine in blastogenesis, cytokine resease and restoration of spleen cells population, and they recommended the therapeutic usefulness of piperine in immuno-compromised situations.…”
Section: Resultsmentioning
confidence: 99%
“…One hundred microliters of the cell suspensions were then added to flat-bottomed 96-well plates (Becton Dickinson, Cockeysville, MD), containing 100 µl triplicate cultures of complete RPMI 1640 or DMEM media (unstimulated controls), the extracts at various concentrations (extracts were dissolved in complete RPMI 1640 (for L5178Y-R cells) or DMEM medium (for B16F10 cells), extract-free vehicles (vehicles were similarly processed as with P. marginatus extracts, but without plant material), and vincristine as a positive control. After incubation for 44 h at 37°C with 5% CO2, MTT (0.5 mg ml -1 , final concentration) was added, and cultures were additionally incubated for 4 h. Next, cell cultures were incubated for 16 h with extraction buffer (100 µl well -1 ) and optical densities, resulting from dissolved formazan crystals, were then read in a microplate reader (DTX 880 Multimode detector, Becton Dickinson, Austria) at 570 nm (Gomez-Flores et al, 2009) …”
Section: L5178y-r and B16f10 Cells Preparation And Culturementioning
confidence: 99%
“…Thymus and spleen were removed immediately after mouse death, and a single cell-suspension was prepared by disrupting the organs in RPMI 1640 medium as previously reported (Gomez-Flores et al, 2009). The cell suspensions were washed three times in this medium, suspended, and adjusted to 1 × 10 7 cells ml -1 in complete RPMI 1640 medium.…”
Section: Cell Preparation and Culturementioning
confidence: 99%
See 1 more Smart Citation
“…Plant metabolites are known to have direct positive effects in the treatment and management of infectious diseases and cancer. In addition, the indirect effects of plant metabolites through immunomodulation are well studied 6 .…”
Section: Introductionmentioning
confidence: 99%